Materialist Premises in Hobbes and Kropotkin for Antipodean Conclusions: The State of War and the Mutual Aid - Francesco Scotognella (European Scientific Journal, ESJ, 2020)
A methodological similarity between Thomas Hobbes and Pëtr Kropotkin is the intention to elucidate a theoretical foundation to a broad audience, in the sense that they are willing to popularize a clear description of the reality and a subsequent political view. To do so, they use a scientific method, deductive (starting from empirical observations) in the case of Hobbes, inductive-deductive in the case of Kropotkin. Kropotkin also underlines the educational value of the scientific method. Although they both start their argumentations from a materialist ontology, Hobbes and Kropotkin conjecture two completely different states of nature. Hobbes describes the state of nature through the two famous metaphors homo homini lupus and bellum omnium contra omnes, while Kropotkin introduced the theory of mutual aid. Hobbes has been influenced by the scientific revolution initiated by Francis Bacon, one of his mentors, and Galileo Galilei. Kropotkin has been influenced by the ground-breaking writings of Charles Darwin together with a very fruitful Russian scientific environment. The disenchanted view of the human nature in Hobbes, a state of war due to the fact that everyone has rights on everything, helps him to legitimate sovereignty, while the positive view of human nature in Kropotkin, a spontaneous mutual aid among people in a community, helps him to legitimate anarchy. Therefore, the fascinating scientific methods of the two materialists Hobbes and Kropotkin to structure a solid political theory cannot neglect different views on human nature due to their historical contexts.